Analysis And Enhancement Of Cracking Resistance In Thermal Barrier Coatings By Functionally Graded Layers (Canadian Institute of Mining, Metallurgy and Petroleum, 2010)
Thermal barrier coating (TBC) systems provide thermal insulation to high temperature for aero¬propulsion. A fracture mechanical model developed earlier for multilayer systems is applied on TBC to realize superior performance by enhancement of fracture resistance. Functionally gradient materials (FGM) solution concept is the basis of approach followed here. A few realistic FGM TBCs are considered in the analysis in addition to a conventional TBC as the base case and a hypothetical worst case with YSZ-YSZ interface. Parameters like number, composition and thickness of graded layers and elastic modulus are considered for the analysis and quantitative improvement of fracture resistance of TBCs. The analysis is confined to deep crack with crack size to width ratio as 0.5.